Study of Mangosteen Peel (Garcinia mangostana L.) Waste Capability to Recover Au(III) and Ag(I) in Aqueous Solution - Mellia Harumi; Rian Kurniawan; Agustiwandina Saputri; Dian Hanna Saraswati; Meissha Ayu Ardini; Sri Sudiono (Indonesian Journal of Chemistry, 2021)
Electronic waste (e-waste) has been confirmed containing some precious metals such as gold and silver. Mangosteen peel waste as eco-friendly adsorbent has been studied to recover Au(III) and Ag(I) successfully. Recovery was started through adsorbent preparation, consisting of soxhlet extraction and maceration. About 100 mg of adsorbent was dispersed into Au(III) and Ag(I) solutions in various pH conditions (2–6). The result proves that the optimum adsorptions of Au(III) and Ag(I) are at pH 2 and pH 6, respectively. Au(III) adsorption follows the isotherm model of Langmuir with a maximum capacity of 0.580 mmol/g (114.27 mg/g). Ag(I) adsorption follows the isotherm model of Freundlich with a maximum capacity of 0.511 mmol/g (55.10 mg/g).